Cardiovascular Properties of the Androgen-Induced PCOS Model in Rats: The Role of Oxidative Stress. (1st September 2021) - Joksimovic Jovic, Jovana; Sretenovic, Jasmina; Jovic, Nikola; Rudic, Jovan; Zivkovic, Vladimir; Srejovic, Ivan; Mihajlovic, Katarina; Draginic, Nevena; Andjic, Marijana; Milinkovic, Milica; Milosavljevic, Zoran; Jakovljevic, Vladimir
Abstract : Polycystic ovary syndrome (PCOS) is a multifaced reproductive endocrinopathy affecting 6-20% of women of childbearing age. It was previously shown that women with PCOS have an increased risk of cardiovascular (CV) diseases. The aim of this study was to evaluate the cardiodynamic parameters of isolated rats' hearts, blood pressure levels, and histomorphological changes in the heart tissue following the androgen-induced PCOS model in rats and the role of oxidative stress in the development of these CV properties of PCOS. 21-day-old female rats (n = 12 ) were divided into control and PCOS groups. PCOS was induced by administration of testosterone enanthate (1 mg/kg BW, daily) during 35 days. During the autoregulation protocol (40-120 mmHg) on the Langendorff apparatus, ex vivo cardiodynamic parameters of retrogradely perfused hearts showed enhanced contractile function and increased lusitropic effects in the left ventricle (LV) in PCOS rats. Systolic and diastolic pressures in LV were elevated at all perfusion pressure values. Systemic arterial systolic blood pressure showed borderline elevation, while mean arterial blood pressure was significantly higher in PCOS rats. Histological evaluation of heart tissue depicted hypertrophic (8.3%) alterations in LV cardiomyocytes and increase (7.3%) in LV wall thickness. Oxidative stress parameters were altered in systemic circulation, coronary venous effluent (CVE), and heart tissue. Levels of superoxide dismutase and reduced glutathione were decreased in blood and heart tissue, while catalase activity was not altered. Degree of lipid peroxidation was increased in circulation as well as heart tissue. Increased levels of O2 - in CVE indicated the cardiotoxic effects in the rat PCOS model. The mentioned alterations of oxidative stress parameters in the blood, CVE, and heart could be recommended as potential contributors underlying the development of CV risk in PCOS women.